Calibrating the Distance-Deterrence Function for the Perth Metropolitan Area - Rasouli, Alireza (Curtin University, 2018)
The Perth metropolitan area and its surrounding regions have been expanding rapidly. With this rapid growth, consideration should be given to strategic modelling. Development of reliable model depends significantly on the calibrated parameters to reflect the existing situation. Deterrence functions play an important role for distribution of the trips and would simulate the trip distances. Therefore they should be calibrated for any particular models. This study aims to review the most common deterrence functions and calibrate them for the work trips.